Moral Justification of Abortion in Early Term Pregnancy: A Consequentialist Approach - Odei, Deborah (Université d'Ottawa | University of Ottawa, 2020)
This paper argues that the fetus has a right to live and that it is morally wrong to terminate a pregnancy even in the first trimester, although in some special cases, abortion becomes a necessity. Abortion is one of the most complicated issues as there has been contradictory views on whether it is the fetus or the mother who has the right to live. Most of the debate are centered around pro-life and pro-choice schools of thought. Proponents of the pro-life view argue against abortion and favor the fetus whereas most of the proponets of pro-choice view argue for the right of the mother and in her favor. This paper generally subscribes to the pro-life’s view on abortion, with the exception that where abortion becomes the only option to save the woman’s life, the abortion must be done. The moral justification of abortion in these special circumstances will be argued using the consequentialist approach. The consequentialist theory, apart from viewing the consequences of one’s action, seeks to maximize happiness and minimize pain. The paper argues that some abortions can be morally justified so long as such process maximies the happiness of the woman and people around her. In effect, this paper seeks to prove that as much as the fetus has the right to life, in some cases, the life of the mother supersedes that of the fetus and it is important to consider these factors when morally judging the action or practice of abortion. The paper concludes that the aftermath of not terminating these pregnancies can lead to problems in the society we live in.